A Descriptive Correlation Study on Stress and Psychological Wellbeing among Nursing Students in Selected Nursing Institutes of Ambala, Haryana - Anamika Gautam1 , Srinivasan.P2 , Gurvinder Kaur3 , Jyoti Sarin4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction-There is widespread recognition that stress can have reflective negative impacts on nurses’psychological well-being. Stressful environment was repeatedly causing a negative effect on the academicperformances and psychological well-being of the nursing studentMethod- A correlation study was selected. Total 120 nursing students were included by disproportionatestratified random sampling. Data was collected by using DASS-42 (14 items of stress) and psychologicalgeneral wellbeing indexResult- Finding of the study showed that there was significant moderate negative correlation between stressand psychological wellbeing.Conclusion-The study concluded there was a significant correlation between stress and psychologicalwellbeing scores among nursing students. Hence, it infers that if stress decreases psychological well beingincreases and vice versa.